Implantação do SWOT para melhoria operacional do serviço de atendimento emergencial de uma distribuidora de energia. - BARROS, Bruno Humberto (2021)
This study aimed to evaluate the process of the Emergency Service (SAE) in a Regional (REG-B) of an Energy Distribution Company (DIST-1), with a focus on the works of Operational Investment (IOP). A Working Group with Managers and Multipliers who worked directly or indirectly in the SAE process was defined, and for this evaluation, the techniques and tools of Quality Management were used, such as Brainstorming, the SWOT matrix, Hypothesis Analysis and preparation of a Plan of Action aimed at evaluating the existing flow and defining the necessary improvements for the results of ANEEL's DEC (Equivalent Duration of Interruption per Consumer Unit) and FEC (Equivalent Frequency of Interruption per Consumer Unit) indicators, and also improvements in the management of Work Closures of the IOP carried out in the distribution system. In the SWOT matrix, it was possible to identify that the Weaknesses should be treated as a priority, as they presented 52% of those appointed by the Working Group, with the Action Plan being directed towards four of the thirteen Weaknesses identified, which represented 40% of what should be addressed. Apart from Brainstorming, the SWOT matrix and Hypothesis Analysis, techniques were also applied, from Routine Management, from the elaboration of Performance Indicators and, finally, a comparison between the results of 2020 and 2021 was carried out.